2016
DOI: 10.1111/jnc.13861
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of adeno‐associated virus vectors across a model of the blood–brain barrier; a comparative study of transcytosis and transduction using primary human brain endothelial cells

Abstract: Developing therapies for central nervous system (CNS) diseases is exceedingly difficult due to the blood-brain barrier (BBB). Notably, emerging technologies may provide promising new options for the treatment of CNS disorders. Adeno-associated virus serotype 9 (AAV9) has been shown to transduce cells in the CNS following intravascular administration in rodents, cats, pigs, and non-human primates. These results suggest that AAV9 is capable of crossing the BBB. However, mechanisms that govern AAV9 transendotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 38 publications
6
73
0
Order By: Relevance
“…Merkel et al . () strengthen their findings by addressing whether AAV9 transcytosis was energy‐dependant. Using cell culture inserts plated with human BMVECs, the authors demonstrated that the movement of AAV9 across the endothelial barrier is impeded at 4⁰C, indicative of metabolic (active) transport, congruent with transcytosis.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…Merkel et al . () strengthen their findings by addressing whether AAV9 transcytosis was energy‐dependant. Using cell culture inserts plated with human BMVECs, the authors demonstrated that the movement of AAV9 across the endothelial barrier is impeded at 4⁰C, indicative of metabolic (active) transport, congruent with transcytosis.…”
mentioning
confidence: 79%
“…In the current issue of J Neurochem , Merkel et al . () investigated trafficking mechanisms of AAV2 and AAV9 across a barrier composed of endothelial cells. Brain microvascular endothelial cells (BMVECs) were isolated from the temporal lobe or hippocampal formation of human subjects seeking operative treatment for epilepsy.…”
mentioning
confidence: 99%
See 3 more Smart Citations